Distribution, pathogenicity and disease control of Fusarium tricinctum - Wang, Yun; Wang, Ruoyu; Sha, Yuexia (Frontiers in Microbiology, 2022)
Plant pathogenic fungi such as Fusarium tricinctum cause various plant diseases worldwide, especially in temperate regions. In cereals, F. tricinctum is one of the most common species causing Fusarium head blight (FHB) and root rot. Infection with F. tricinctum results in high yield losses and reduction in quality, mainly due to mycotoxin contamination of grain. Mycotoxins produced by F. tricinctum, such as enniatins (ENs) and moniliformin (MON), which are the most studied mycotoxins, have been reported to have multiple toxic effects on humans and animals. Although chemical control of Fusarium infection has been applied to grains, it is not always effective in controlling disease or reducing the level of mycotoxins in wheat grains. To the contrary, chemical control may significantly increase infection of F. tricinctum in fungicide-treated plots after treatment. Our studies show that the bacterium Bacillus amyloliquefaciens, has good control effects against F. tricinctum. Therefore, its use as a biological control agent against various plant pathogens may be an effective strategy to control the spread of Fusarium pathogens. Here, we conduct a review of the literature involving this plant pathogen, its diversity, virulence, and methods to control.